The effects of entrepreneurial management, entrepreneurial orientation and ethics on the women-owned SMEs business performance in Malaysia - Umi Kartini, Rashid (2017)
Being one of the major players in economic growth, the number of women-owned SMEs in Malaysia is increasing and researches are directed on their business performance. Notwithstanding the vital importance of this area, very few studies have been done to look at the relationships between entrepreneurial management, entrepreneurial orientation and ethics, and the performance of women-owned businesses particularly in Malaysia. Therefore, this study focused primarily on testing the possibility of ethics as the mediating variable in the relationships between entrepreneurial management and entrepreneurial orientation, and women-owned SMEs business performance. Based on the literature, six dimensions of entrepreneurial management: entrepreneurial culture, growth orientation, management structure, resource orientation, reward philosophy, and strategic orientation; and three dimensions of entrepreneurial orientation: innovativeness, pro- activeness and risk taking, were selected, and 18 direct and indirect hypotheses were developed. Measurement tools were based on scales previously established in the literature for measuring entrepreneurial management, entrepreneurial orientation, ethics, and also business performance. A total of 207 usable data were gathered through a mail questionnaire survey, and multiple regressions analysis was employed to analyse the data. The empirical findings revealed significant relationships between women-owned SMEs business performance and resource orientation, reward philosophy, strategic orientation, innovativeness, pro-activeness as well as risk taking. Ethics was found to mediate the relationships between reward philosophy, strategic orientation, pro-activeness, risk taking and women-owned SMEs business performance. The research framework of this study contributes to the existing body of knowledge of women entrepreneurs and entrepreneurship literature. The theoretical contributions and practical implications are also significant findings for women owners-managers of SMEs and women entrepreneurial development in the country. Finally, some limitations are also acknowledged that indicate future research directions.